SEMI QUANTITATIVE AND QUANTITATIVE ANALYSIS OF ROCKSLIDES AT PONOROGO - PACITAN ROAD KM 226 - Retno Puspa Rini; Arief Rachmansyah; Eko Andi Suryo (Rekayasa Sipil, 2022)
Rock avalanches is one of the problems that is often faced along the Ponorogo - Pacitan road. The research location was at KM 226 which is located at coordinates 111°22'14.39" East Longitude and 08°01'14.73" South Latitude. Semi quantitative analysis was conducted by using Geology Strength Index method, that is based on field identification. The quantitative slope stability analysis was used Rocscience software consisting of Roclab and Rocplane used the Hoek and Brown method. The classification results of  rock mass GSI obtained value of 25 and was dacite rock type. The slope had angle of 75o and  height of 12 meters, safety factor (FK) of 1.065 was obtained which made the slope unstable, so prevention was done by changing the slope angle geometry based on variations of 75 o - 35 o, so that (FK) 35o = 1.52